2017
DOI: 10.3390/su9071197
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Members of Generation Y to Destination Brands: A Case Study of the CUBIS Project

Abstract: There is direct correlation between building powerful destination brands and the degree to which tourists and locals share the brands values. The massive penetration of the active population by Generation Y has generated a major shift in tourism marketing, based on the profile of this cohort. The members of Generation Y are very different from previous generations. The so-called "digital natives" share high technological proficiency; they like to share their skills; they are disloyal consumers; and they are af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…These ranks, as well as the results of the focus-group discussions presented in this paper support the conclusion formulated by Vaiman and Holden in 2011 [25] regarding the fact that talent management is new in most Central and Eastern European countries. The generational delay identified in these countries might be a possible explanation [8]. The two cases presented in the article demonstrated that hotels in Western European countries started to align their talent practices to the new psychological contract; they have responsibly correlated their informal obligations with the new needs and expectations of their potential and real employees.…”
Section: Future Directions For Research and Practical Implicationsmentioning
confidence: 88%
See 2 more Smart Citations
“…These ranks, as well as the results of the focus-group discussions presented in this paper support the conclusion formulated by Vaiman and Holden in 2011 [25] regarding the fact that talent management is new in most Central and Eastern European countries. The generational delay identified in these countries might be a possible explanation [8]. The two cases presented in the article demonstrated that hotels in Western European countries started to align their talent practices to the new psychological contract; they have responsibly correlated their informal obligations with the new needs and expectations of their potential and real employees.…”
Section: Future Directions For Research and Practical Implicationsmentioning
confidence: 88%
“…There is no consensus regarding the exact birth years of each generation from the present generational cycle and research has also demonstrated that there is a generational delay in developing economies, compared to the developed ones [8]. The generational theory is not an age-related theory-because it is not the age which first differentiates the individuals from different generations, but the context (social, economic, political etc.)…”
Section: The Generational Theory and Its Popularity In Human Resourcementioning
confidence: 99%
See 1 more Smart Citation
“…Young consumers are a very unpredictable group in terms of decision-making and purchasing habits, characterized by a low degree of loyalty (Bochert, Cismaru, Foris, 2017) 6 and continuously confronted with a wide variety of products (Veríssimo, Costa, 2018). This represents a significant challenge for businesses and providers of tourism and hospitality services.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Higher loyalty as well as understanding of employee engagement are typical features of experienced employees. Recently, many authors have been dealing with the issue of generation gap in the workplaces (Dabija et al, 2018;Naim & Lenka, 2018;Bochert et al, 2017;Rani & Samuel, 2016;Berkup, 2014;Festing & Schäfer, 2014;Bolton et al, 2013;Cennamo & Gardner, 2008). There are various views, approaches and attitudes as the enterprise is a multigenerational workplace and each individual generation has developed its own set of expectations, needs, values and working style.…”
Section: Theoretical Frameworkmentioning
confidence: 99%